Occlusal considerations and principles in Dental Implant: A Review of Literature - Om Prakash (NMO Journal)
In today's world dental implant have been used widely. Occlusion plays a central role in clinical dentistry and is essential for normal physiologic function. Occlusion in implantology is a very important factor to be considered during treatment planning. This paper summarizes current knowledge on how implant protected occlusion is a very important criteria to obtain an improved longevity of both the dental implant and prosthesis.